Deconstructing the Gentleman Amateur. (27th May 2021) - Stone, Duncan
ABSTRACT: The concept of the gentleman amateur is an important aspect of upper and middle-class Victorian and Edwardian male identity. Although he remains a significant literary presence today, the form and length of time the gentleman amateur remained a cultural influence in society is contested. This article examines one realm of this influence – sport – in terms of the social and philosophical origins of these titles, what they meant in practice and the repercussions their use had on class cultures, British (English) sporting values and success. It proposes that the gentleman amateur remains a major influence upon British sport today.